WARS OF THE 21ST CENTURY: THEORETICAL APPROACHES, REALITY, AND PROSPECTS - Guliev, Bebir (Revista Inclusiones, 2019)
This article substantiates the need to study wars of the 21st century in the context of the formation of the latest models of warfare. The author reviews the fundamental changes occurring in the theoretical aspect of the approach to this problem. Using military scientific concepts, the author explains the latest approaches and concepts of war and the new (asymmetric) paradigm of military operations, as well as considers their place in the military doctrines of different countries. In the context of new theories of war, the article touches upon some aspects of the Nagorno-Karabakh conflict between Armenia and Azerbaijan. In conclusion, the author attempts to systematize the features of postmodern wars and reflects on the possible prospects for the development of this social phenomenon.